Influential The Dynamics of Religiosity of Online Game Players Mobile Legends: Bang Bang in Kudus - Fanani, Ahmad Farid (Asketik: Jurnal Agama dan Perubahan Sosial, 2025)
Initially, online games were engaged solely to occupy leisure time or for pure entertainment. However, contemporary evidence suggests that online games have become an integral facet of many individuals' lives, particularly among adolescents. Mobile Legends: Bang Bang has emerged as one of the most downloaded games and boasts the highest number of monthly active users in Indonesia. This study aims to examine the impact of online games on the religiosity levels of adolescents. Utilizing an explanation quantitative approach, this article utilizes statistical methods to explore the relationship between online game engagement and religiosity among adolescents. The study's participants were adolescents aged 16 to 18 years from Kudus. Surveys were distributed to collect data, and the statistical analysis was conducted using SPSS 23 for Windows software. The results indicated a statistically significant relationship between the engagements with the mobile game Mobile Legends: Bang Bang and the religiosity of adolescents. This association was further confirmed by the statistical test, which yielded a value of tcount (4.296) greater than the tabulated tvalue (2.000) at a significance level of 0.000 <0.005. This finding suggests a signifikan impact of mobile legends: bang bang on the religiosity levels of adolescents, with a percentage level of 29.1%.